PENERAPAN ALGORITMA DJIKSTRA DALAM MENENTUKAN RUTE TERPENDEK FASILITAS KESEHATAN YANG MELAYANI PASIEN BPJS BERBASIS WEB DI KOTA SUKOHARJO - Kusumastuti, Ratna Tria; Hasbi, Muhammad; Widada, Bebas (STMIK Sinar Nusantara, 2024)
The city of Sukoharjo has health service facilities that serve BPJS patients spread throughout the city of Sukoharjo. The difficulty of determining the shortest distance arises because there are many paths that exist at each location because in fact from location A to location Z there is not only one path, there are many paths that can be passed to form a network. So a system for finding the closest route to health facilities was made that serves Web-based BPJS patients with the aim of making it easier for the verifier staff to guarantee BPJS Health benefits in carrying out their duties and authorities in providing guarantees to participants and related health facility associations.Dijkstra's algorithm is one of the algorithms for determining the shortest route from one health facility location to another. The system is designed using flowcharts and UML (Unfield Modeling Language) using the Google Maps API to display maps, display pins, find and display the closest route using latitude and longitude from Google Maps. The test results in terms of system menu functionality on black box testing, the function of the menus on the system works well. Meanwhile, for the test of the shortest route calculation system, a comparison is used from the results of the system calculations made with the djikstra algorithm with the results of manual calculations using the Dijkstra algorithm. So that the accuracy of the success rate of the system using the djikstra algorithm reaches 92%.